Hubungan Kepuasan Kerja dengan Turnover Intentions pada Perawat Rumah Sakit Dhuafa - Inge Mardiana; Aida Vitayala S. Hubeis; Nurmala K Panjaitan (Institut Pertanian Bogor, 2014)
Government policy through the National Health Insurance program (JKN) needs to be responded to maintain providing the best health services for the community. Best health services can be provided by the fulfillment of the human resources (HR) such as nurse either in the quality and quantity. Currently Dhuafa Hospital (RS Dhuafa) is still difficult to meet the number of nurses requirement. Highly turnover rate of nurses occured in the period January to December 2013. It is clearly important to know the causes, among other factors of job satisfaction. In theory, job satisfaction is one of the factors that may influence the tendency of employee to decide to get out of work. Based on this background, the study was conducted to determine how the relationship between job satisfaction and highly intentions of nurses turnover rate in Dhuafa Hospital. The purpose of this study are to analyze the relationship between job satisfaction and nurses turnover rate in Dhuafa hospital, and also to find out the most dominant factors on turnover intentions. This research is done by statistical methodology using the correlation, descriptive approach and test the hypotheses that have been formulated previously. Data collection will be exercises by questionnaire and interview techniques, and will be analyze using Partial Least Square (PLS). The results showed that in general, nurses were satisfied geeting work in Dhuafa hospital, although less of payments and promotion opportunities were insists. Those factors were the trigger of job satisfaction to them. In general, the study conclude that although the nurses turnover in Dhuafa hospital were getting intense but they still have highly survival rate to work in Dhuafa hospital